Molecular Characterization of Echinococcus Granulosus Isolated from Human Hydatid Cyst Using Mitochondrial Cox1 Gene Sequencing in Dohuk Province- Kurdistan Region, Iraq - AHMED, BAYRAM D.; MERO, WIJDAN M.S.; SALIH, A.M.; XIAO, NING; CASULLI, ADRIANO; ABDO, JASIM M. (Science Journal of University of Zakho, 2013)
To characterize the circulating E. granulosus genotype in Duhok province, a total of 17 human (14 female and 3 male) hydatid cysts (10 from lung and 7 from liver) were subjected to molecular analysis using mitochondrial cox1 gene sequencing. Total DNA was extracted using Qiagene DNeasy blood and tissue mini kit then it was electrophoresed on 1.5% Agarose gel in TBE 0.5% buffer for 20 minutes and sequenced. Variable sequences of 418bp were obtained for 15 out of 17 samples. The sequences were aligned with old sequences of G1, G2, G3 genotypes and the new Turkish and Iranian genotypes. As a result, the Duhok isolates were more identical to the newer Turkish and Iranian G1 common sheep genotype sequences than the old ones due to the occurrence of different multiple nucleotide substitutions among nearly half of Duhok isolates. In conclusion, the results of this study showed the presence of the G1-G3 cluster sensu stricto cluster genotype in Duhok province, therefore preventive measures should be arranged accordingly.